AFF1 inhibits adipogenic differentiation via targeting TGM2 transcription. (22nd May 2020) - Chen, Yaqian; Wang, Yuan; Lin, Weimin; Sheng, Rui; Wu, Yunshu; Xu, Ruoshi; Zhou, Chenchen; Yuan, Quan
Abstract: Objectives: AF4/FMR2 family member 1 (AFF1), known as a central scaffolding protein of super elongation complex (SEC), regulates gene transcription. We previously reported that AFF1 inhibited osteogenic differentiation of human mesenchymal stromal/stem cells (hMSCs). However, its role in adipogenic differentiation has not been elucidated. Materials and methods: hMSCs and 3T3‐L1 pre‐adipocytes were cultured and induced for adipogenic differentiation. Small interfering RNAs (siRNAs) were applied to deplete AFF1 while lentiviruses expressing HA ‐ Aff1 were used for overexpression. Oil Red O staining, triglyceride (TAG) quantification, quantitative real‐time PCR (qPCR), Western blot analysis, immunofluorescence staining, RNA sequencing (RNA‐seq) analysis and ChIP‐qPCR were performed. To evaluate the adipogenesis in vivo, BALB/c nude mice were subcutaneously injected with Aff1 ‐overexpressed 3T3‐L1 pre‐adipocytes. Results: AFF1 depletion leads to an enhanced adipogenesis in both hMSCs and 3T3‐L1 pre‐adipocytes. Overexpression of Aff1 in 3T3‐L1 cells results in the reduction of adipogenic differentiation and less adipose tissue formation in vivo. Mechanistically, AFF1 binds to the promoter region of Tgm2 gene and regulates its transcription. Overexpression of Tgm2 largely rescues adipogenic differentiation of Aff1‐ deficient cells. Conclusions: Our data indicate that AFF1 inhibits adipogenic differentiation by regulating the transcription of TGM2.